Effect of 980nm Low-Level Laser Therapy on Matrix Metalloproteinase-1 Levels in Gingival Crevicular Fluid During Fixed Orthodontic Treatment: MMP-1 modulation in GCF following low-level laser therapy - Agha Aghili, Hossein; Zadbin, Fariba; Yassaei, Soghra; Babaei Zarch, Ehsan (Journal of Lasers in Medical Sciences, 2025)
Introduction: Given the unique biostimulatory effects of low-level lasers, particularly on collagen production and fibroblast activity, this study aimed to measure the changes in MMP-1 levels in response to low-level laser therapy (LLLT) in individuals undergoing orthodontic treatment. The increase in MMP-1 may signal beneficial tissue adaptation to orthodontic force. Methods: This double-blind, randomized clinical trial included 22 individuals referred to the orthodontic department of Yazd Faculty of Dentistry who required fixed orthodontic treatment. The left and right mandibular anterior teeth of patients meeting the inclusion criteria were randomly assigned to the intervention and control sides. A low-level diode laser (980 nm, 100 mW output power) was applied to two teeth in the intervention group for two consecutive days. Gingival crevicular fluid (GCF) samples were collected from both sides at 24 hours (T1) and 164 hours (T2) post-irradiation. MMP-1 levels were measured using ELISA. Data were analyzed using SPSS software with independent and paired t-tests, with a significance level set at 0.05. Results: At T1, the mean MMP-1 level in the intervention group was 6.77±0.54 ng/mL, which was significantly higher than the control group’s level of 6.15±0.40 ng/mL (P<0.001). At T2, the mean MMP-1 level in the intervention group (6.20±0.62 ng/mL) was not significantly different from that in the control group (6.21±0.55 ng/mL) (P=0.960). The average MMP-1 level in the control group did not differ significantly between T1 and T2 (P=0.546). However, the mean MMP-1 level in the intervention group at T1 was significantly higher than at T2 (P<0.001). Conclusion: MMP-1 levels in GCF increase temporarily after low-level laser irradiation with orthodontic force, indicating a potentially beneficial effect on tissue remodeling. Levels return to baseline by 164 hours, suggesting a controlled, short-term response.